The Trafficking of Men in Cambodia: How Masculinities Challenge Notions of Victimhood - Eastmond, Oonagh (My University, 2016)
This paper addresses the exploitation of Cambodian men on Thai fisher boats. Exploitation is enabled through gender stereotypes that prohibit Cambodian men to identify themselves as victims. In addition, institutions dealing with legal support of victims are based on gender stereotypes. Thus, mainly sexual exploitation and female victims are focused by organizations of support and the state. There are no legal regulations to persecute exploited men and trafficking of men.
Keywords: Ausbeutung; Geschlechterrolle; Männlichkeit; masculinity; ddc:300